2017
DOI: 10.1007/s11207-017-1071-x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Solar Coronal Rotation with Altitude – Revisited

Abstract: Here we report in depth reanalysis of a paper by Vats et al. (2001) [Astrophys. J. 548, L87] based on the measurements of differential rotation with altitude as a function of observing frequencies (as lower and higher frequencies indicate higher and lower heights, respectively) in the solar corona. The radial differential rotation of the solar corona is estimated from daily measurements of the disc-integrated solar radio flux at 11 frequencies: (275, 405, 670, 810, 925, 1080, 1215, 1350, 1620, 1755 MHz and 28… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
5
16
2
Order By: Relevance
“…the sidereal coronal rotation period increases with increasing frequency. However, by using the same data sets, Bhatt et al (2017) found that the solar corona rotates more slowly at higher altitudes, which contradicts the conclusion given by Vats et al (2001). By studying the coronal rotation period as a function of latitude between ±60 • for the period from 1999 to 2001, Chandra et al (2009) found that the solar corona rotates less differentially than the photosphere and chromosphere.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…the sidereal coronal rotation period increases with increasing frequency. However, by using the same data sets, Bhatt et al (2017) found that the solar corona rotates more slowly at higher altitudes, which contradicts the conclusion given by Vats et al (2001). By studying the coronal rotation period as a function of latitude between ±60 • for the period from 1999 to 2001, Chandra et al (2009) found that the solar corona rotates less differentially than the photosphere and chromosphere.…”
Section: Introductionmentioning
confidence: 79%
“…The slightly difference of the rotation period length between the Fe XIV green line emission and the solar radio flux at 2800 MHz can be interpreted as the following reason. The 10.7 cm solar radio flux is directly related to the total amount of the magnetic flux, which should be originated from the lower (inner) corona at the 60 000 km above the surface atmosphere (Vats et al 2001;Bhatt et al 2017). However, the Fe XIV green line emission arises in coronal material with a characteristic temperature of about 1.8 ×10 6 K (Jordan 1969), which is the typical temperature of most of the corona outside of the coronal holes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vats et al (2001), uses disk-integrated simultaneous measurements of solar radio flux for the frequency range of 275-2800 MHz and showed a strong dependence of the coronal rotation period on the heights in the corona, i.e., the sidereal coronal rotation period increases with an increase in height in the solar atmosphere. While Bhatt et al (2017) contradict the result by using the same data set and obtained that solar corona rotates slower at higher altitudes. By analyzing the coronal rotation period as a function of latitude between ±60• for the period 1999-2001, Chandra et al (2009) obtained that as compared to the photosphere and chromosphere, solar corona rotates less differentially.…”
Section: Introductionmentioning
confidence: 59%
“…Solar radio fluxes emanated at different heights are also used to find out the temporal and spatial change of coronal rotation (Vats et al 1998(Vats et al , 2001Chandra et al 2009;Chandra, & Vats 2011;Li et al 2012;Xie, Shi & Zhang 2017;Bhatt et al 2017Bhatt et al , 2018. The rotation of the solar corona can also be used as an indicator of the differential rotation of subphotosperic layers.…”
Section: Introductionmentioning
confidence: 99%